Perceived Effects of Job Stress on the Well-Being of Health Workers in Baruten Local Government Area Kwara State, Nigeria - I.I. Kperogi; J.F. James; A.M. Abdulraheem; I. Ologele; S.A. Adeoye; M.O. Ibrahim (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. This study examined perceived effects of job stress on the well-being of Health Workers (HWs) in Baruten Local Government Area (L.G.A) Kwara State, Nigeria. Workplace stress is the harmful physical, mental or social responses that happens to employees when there is pressure of job demands against the amount of control employees have on meeting them. These has caused so many effects on general wellbeing of employees across the world. Methods. This study adopted descriptive survey research design. A researchers’ structured questionnaire, which was validated and tested for reliability with 0.81r, was used for the study. Descriptive and inferential statistics were used to analyse the research questions and hypotheses. Hypotheses I and II respectively stated that HWs in the L.G.A, do not significantly perceive that job stress have effects on their physical, mental and social wellbeing. Results. Hypotheses I and II respectively has a calculated chi-square value of 294.16 which is greater than table value of 16.92 (Cal χ2 val ˃ Tab χ2 val) and a calculated chi-square value of 361.82 which is greater than table value of 16.92 (Cal χ2 val ˃ Tab χ2 val) all @ 9 degree of freedom. This shows that the two hypotheses were all rejected, implying that HWs significantly perceive that job stress have effects on their physical, mental and social wellbeing. Conclusion. Conclusively, HWs in the L.G.A, perceive that job stress affects their general wellbeing. Recommendations were drawn from the conclusion to include admonishing Baruten L.G.A management to urgently work towards improving workers’ ability to cope and manage stressful situations through stress management programs among others.